Perancangan Sistem Sensor Pemonitor Lingkungan Berbasis Jaringan Sensor Nirkabel - Nurhuda Maulana; Oky Dwi Nurhayati; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2016)
Air pollution is a problem that get a lot of people’s attention, especially at campus environment. It is evocate the stakeholder of campus to monitor the environmental conditions at the campus which themed a green campus. Advances in science and technology, especially in computer and embedded systems in principle can be applied to solve this problem. There are creating an application system that is equipped with sensor to monitor the air quality level wirelessly. The system supports several environmental monitoring sensors that are connected in a wireless sensor network. The objective of this research was to design and create a sensor system that can monitor environment condition quantity by providing the appropriate output value. Sensors that used to read the air quality parameters is TGS 2600 to read the gas concentration of carbon monoxide (CO), TGS 2201 for nitrogen dioxide (NO2), GP2Y1010AU0F for particulate matter, BH1750 for light ambient, and SHT11 for humidity and temperature. This sensor system using Arduino board that based on Atmega 2560 microcontroller. This system is equipped with RTC as a time and GPS as a coordinate where the sensor system is placed as a node. The result of this reseach is the system able to read parameters as air quality monitoring well. The error reading in this sensor system is 0.69 ppm CO gas, 2.8 lx on the intensity of light, 0.22 C in temperature reading, and 0.98% in humidity readings.